The Relationship Between Occupational Stress and Quality of Care Among Emergency Department Nurses in Government Hospitals - Sae’d M. Abu El-Kass; Lama Abu El-Kass; Nasayem Alswarka; Sabah Abu Behiri; Aysha Alderawy; Tahreer Abu El Khair; Maram Alaraj; Nibal Aldahdouh (SAGE Open Nursing)
Background Occupational stress is a prevalent health issue that can have both clinical and psychological repercussions, impacting the quality of care of emergency nurses. However, more research is required to better understand the prevalence of this condition and its implications for the work capabilities of nurses in emergency departments. Objective To examine the relationship between occupational stress and the quality of care among emergencydepartment nurses at government hospitals in the Gaza Strip, Palestine. Methods A descriptive cross-sectional design was used to examine stress levels and quality of care using the convenience sampling technique between July and September 2023. Nurses completed a questionnaire comprising three parts: Emergency nurse stress questionnaire with 12 items, professional quality of life scale with 10 items, and demographic data with 9 items in three governmental hospitals in the GazaStrip. Statistical analysis was carried out using SPSS version 25. Result A total of 80 emergency nurses were included. The study showed an equal distribution of emergency nurses according to gender 50%. Furthermore, 42% of the nurses working at Al Shifa Medical Hospital, more than half 54%, had less than 5 years of experience. The overall average mean score for the level of stress among emergency nurses was 4.83 (SD = 1.078), Also, the overall average mean score quality of care for among emergency nurses was 2.51 (SD = 0.984). Conclusion This study indicates that there was a significant negative relationship between occupational stress at work and quality of care, indicating that as stress levels increase, factors that restrict quality of care also increase. Furthermore, the findings highlighted statistically significant differences in the mean score of occupation stress and age, sex, years of experience and shift of work. Based on these results, it is essential that health policymakers address the high levels of OS among emergency nurses to improve quality of care.